과학과 관련된 사회ㆍ윤리적 주제 교수에 대한 과학, 사회, 윤리 교사들의 인식 - 유정숙, 최성연, 이현주 (교과교육학연구, 2011)
본 연구는 과학과 관련된 사회ᆞ윤리적 주제(SSI)의 본성과 밀접한 과학, 사회, 윤리 교사들이SSI를 자신의 교과 수업에서 가르칠 때 교사의 전공에 따라서 SSI 교수에 대한 인식이 어떻게 다른지에 대해 탐색하고, 이를 통해 과학 및 기타 관련 교과에서 효과적인 SSI 교수를 할 수 있는 방안을 제안해보고자 하였다. 즉, 과학, 사회, 윤리 교사들이 과학과 SSI에 대해 어떻게 이해하고 있으며, 왜 SSI를 수업에 다루는지, 그리고 SSI를 수업에 도입할 때 무엇에 강조점을 두는지 등에 대해알아보았다. 본 연구에는 SSI 교수 경험이 있는 과학, 사회, 윤리(도덕) 교과 교사 총 15명(교과 당5명)이 참여하였으며, 반구조화된 개별 면담을 실시하여 자료를 수집하였다(각 교사 당 60분에서150분 정도 소요). 연구 결과, 과학, 사회, 윤리 교사들은 SSI 교수에 대해 공통적인 인식을 보이는부분도 있었으나, 교과별 특성과 관련되어 다음과 같은 몇 가지 차이점을 보였다. 첫째, 과학과 SSI 에 대해 세 교과 교사들은 모두 현대 사회에서 과학이 다양한 사회 측면 및 윤리적인 가치들과 복잡하게 얽혀 있다는 것에 동의하였다. 그러나 교사들은 과학 자체가 무엇이며 어떤 특성을 지녔는지에 대한 이해가 다소 부족하였다. 둘째, 대부분의 참여 교사들은 교사의 개인적 신념이나 경험,개인이 인식하는 교과의 목표와의 연관성에 대한 인식 등을 계기로 SSI 수업을 시작하게 되었다고응답하였다. 과학 교사의 경우에는 SSI 교수에 대한 개인적 신념이나 관련 경험을 더 많이 언급한반면, 사회나 윤리 교사들은 SSI 교수를 개인이 인식하는 교과의 특성과의 부합성을 더 많이 언급하였다. 셋째, 교과별로 교사들이 자주 활용하는 SSI 주제 및 교수 목표 및 강조점에 교과별 특성이 나타남을 알 수 있다. 즉, 과학 교사와 사회 교사들은 지식과 사고기술을 강조하는 반면, 윤리교사들은 사고기술과 가치 태도를 강조하는 경향을 보였다. SSI 자체가 간학문적 성격을 띤 비구조화 된 문제를 의미하기 때문에 효과적인 SSI 교수를 위해서는 SSI의 본질적 특성을 충분히 살릴수 있는 요소들, 즉 가치판단 및 의사결정과 같은 사고 기술, 그리고 윤리의식이나 공감적 태도와같은 가치 태도 부분도 고려되어야 하겠다. This study investigated the perceptions of science, social studies, and ethics teachers on teaching socio-scientific issues (SSI) and the characteristics of their SSI instruction. Based on a comparison among the teachers having different subject identities, the intent was to suggest larger perspectives for SSI instruction. In order to achieve the aim, we focused on three aspects:1) how and in what ways teachers understood science and socio-scientific issues, 2) how did teachers become involved in SSI teaching, and 3) upon which aspects do teachers put more emphasis when addressing SSI. Fifteen teachers (five teachers in each subject) participated in the study. Data was collected by individual interviews lasting between 60 and 150 minutes. The results indicated that: first, most of the teachers agreed that science is interwoven with the various societal sectors and the diverse values of interest groups in contemporary society;however, they lacked an understanding of the nature of science. Second, most of the teachers addressed SSI in their classes as a result of personal motivation and experiences. Whereas science teachers tended to mention their personal conviction for SSI teaching and related past experiences, social studies and ethics teachers tended to note the potential of SSI teaching to meet the educational goals of their subject. And third, science and social studies teachers tended to focus on improving knowledge and thinking skills through SSI instruction, while ethics teachers put more emphasis on nurturing values and character. In order to effectively address SSI, teachers should consider the importance of thinking skills (decision-making, value judgments, etc.) and values/attitudes (compassion, openness, etc.) as well as related knowledge. KCI Citation Count: 7